ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN (Studi empiris pada perusahaan-perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Cahya Ruwita; Puji Harto (Diponegoro Journal of Accounting, 2013)
This research aims to get empirical proof about the factors which are influence corporate risk disclosure in manufacture firms. Corporate characteristic used in this research are size, profitability degree, leverage degree, liquidity degree, financially expertise of audit committees, frequency of audit committees meeting, public ownership structure, type of corporate ownership. This research uses purposive sampling to carry out sample selection. There are 99 manufacture firms which are listed in BEI (Bursa Efek Indonesia) period of 2009 until 2011 become the sample in this research. Stakeholder theory is used to explain relationship inter variable. Risk disclosure in this research use content analysis based on identification of sentences act of risk disclosure in the annual report. Statistic method that used for examining the hypothesis is multiple regression analysis. The result of this research showed that size and profitability degree are positive related significant with corporate risk disclosure. Frequency of audit committees meeting is negatively significant with corporate risk disclosure, while leverage degree, liquidity degree, financially expertise of audit committees,  public ownership structure, type of corporate ownership are not significant with corporate risk disclosure.